CARICOM on the eve of the twenty-first century: where are we, and where are we going?: address at the eleventh annual Private Sector Banquet, Jack Tar Village Resort, St. Kitts, Saturday 27 March 1993 - Carrington, Edwin W. (CCS GeorgetownGT, 1993)
Addresses three major questions, viz. what is CARICOM, who is CARICOM and for whom is CARICOM. Sketches CARICOM's background, origins and essential features; perceives the entire population of the CARICOM community as being CARICOM and targets the youth as the major beneficiaries.